Heteromultimeric CLC chloride channels with novel properties - Lorenz, Claudius (The National Academy of Sciences of the USA, 1996)
The skeletal muscle chloride channel CLC-1 and the ubiquitous volume-activated chloride channel CLC-2 belong to a large gene family whose members often show overlapping expression patterns. CLC-1 and CLC-2 are coexpressed in skeletal and smooth muscle and in the heart. By coexpressing CLC-1 and CLC-2 in Xenopus oocytes, we now show the formation of novel CLC-1/CLC-2 heterooligomers that yield time-independent linear chloride currents with a chloride → bromide → iodide selectivity sequence. Formation of heterooligomeric CLC channels increases the number and possible functions of chloride channels.